The Measurements of Maxillary Alveolar Bone Density at 13-15 Years Age by Using Spiral Computerized Tomography - Farage, Azhar A; Al Fatlawi, Fakhri A (Journal of Baghdad College of Dentistry, 2016)
Background: Bone density is a major factor that affect mini implant primarily stability; no Iraqi studies have evaluated bone density related to mini-implant placement for orthodontic anchorage at age 13 -15 years. The present research aims to evaluate gender, side and site differences in the bone density at various orthodontic implant sites for the maxillary alveolar bone. Materials and methods: Twenty nine individuals (16 males and 13 females) had subjected to clinical examination, then 64-multislice computed tomography scan data were evaluated and bone density was measured in Hounsfield unit at 21 points (9 points for each side and 3 points between the right and left central incisors) . Results: The results obtained showed that there are no significant differences in bone density between males and females and between the left and right sides were found. There was no significant differences in bone density between the maxillary buccal cortical bone and the palatal cortical bone were generally except that at lateral incisor and canine point where the palatal side had higher bone density than buccal side. The mean bone density of the cancellous bone in the anterior part was higher than that in the posterior of the maxilla. Conclusions: When orthodontic, mini implant are indicated, no gender and side difference affect the success rate regarding bone density.